The Millennials Luxury Brand Engagement on Social Media: A Comparative Study of Brazilians and Italians - Casagrande Yamawaki, Melissa Akemi; Sarfati, Gilberto (Internext, 2019)
Over the last decades, social media has become one of the most popular online activity among consumers worldwide, leading companies to adapt and evolve their strategies in other to engage the consumer through new medias. Considering the online environment, the social media has a key participation when building consumer brand engagement. Consumers can develop three roles in this situation: consumer, contributor or creator of content. This empirical study aims to understand and compare the consumer brand engagement of millennials in luxury brands on social media between Brazil and Italy. The luxury brands chosen are Louis Vuitton, Chanel, and Prada and the social medias are Facebook, Twitter, YouTube and Instagram. The study used a quantitative research design, with a questionnaire survey. We collected 438 valid answers. The results do not suggest a relationship between culture and consumer brand engagement on luxury brands through social media among millennials from Brazil and Italy. It is possible that cultural differences were not significant in this study because the brands were not able to engage millennial consumers in both countries or because millennials have a low engagement with brands online.